2017
DOI: 10.1016/j.cell.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM Structure of a Pre-catalytic Human Spliceosome Primed for Activation

Abstract: Little is known about the spliceosome's structure before its extensive remodeling into a catalytically active complex. Here, we report a 3D cryo-EM structure of a pre-catalytic human spliceosomal B complex. The U2 snRNP-containing head domain is connected to the B complex main body via three main bridges. U4/U6.U5 tri-snRNP proteins, which are located in the main body, undergo significant rearrangements during tri-snRNP integration into the B complex. These include formation of a partially closed Prp8 conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
326
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(370 citation statements)
references
References 66 publications
17
326
0
4
Order By: Relevance
“…The region around the cryptic 3′ splice site coincides with an enrichment of adenosines that also appear to have stronger base‐pairing affinity with the cognate U2 snRNA relative to the region around the canonical BPS. Structural analyses of the human and yeast spliceosome in the RNA‐bound B‐activated Complex suggest that cancer‐associated mutations in SF3B1 change the charge and shape of the corresponding amino acid residues that results in direct disruption of the local interaction with pre‐mRNA . This results in a spatial shift in the pre‐mRNA by approximately 10 nucleotides, consistent with bioinformatic predictions.…”
Section: Effects Of Somatic Mutations In Splicing Factorssupporting
confidence: 69%
“…The region around the cryptic 3′ splice site coincides with an enrichment of adenosines that also appear to have stronger base‐pairing affinity with the cognate U2 snRNA relative to the region around the canonical BPS. Structural analyses of the human and yeast spliceosome in the RNA‐bound B‐activated Complex suggest that cancer‐associated mutations in SF3B1 change the charge and shape of the corresponding amino acid residues that results in direct disruption of the local interaction with pre‐mRNA . This results in a spatial shift in the pre‐mRNA by approximately 10 nucleotides, consistent with bioinformatic predictions.…”
Section: Effects Of Somatic Mutations In Splicing Factorssupporting
confidence: 69%
“…Also, DNAJA1 has been related to positive regulation of virus replication in humans (42). SMU1 is also involved in pre-mRNA splicing as a component of the spliceosome and is required for normal mitotic spindle assembly and mitosis (43). Therefore, the modification of the intergenic region of DNAJA1 and SMU1 may disturb the expression of DNAJA1 and SMU1 in the genome-modified chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this method provides the ability to investigate splicing regulation through intron retention, which was previously not possible due to the transient nature of these RNA species and mutations that had to be made for stabilization. Further advances in our understanding of splicing have occurred through recently solved structures characterizing the spliceosome in different forms (Agafonov et al, ; Bertram, Agafonov, Dybkov, et al, ; Bertram, Agafonov, Liu, et al, ; Finci et al, ; Galej et al, ; Nguyen et al, , ; Ohi, Ren, Wall, Gould, & Walz, ; Pomeranz Krummel, Oubridge, Leung, Li, & Nagai, ; R. Wan et al, ; Yan et al, ). More in‐depth reviews of structural studies of the spliceosome can be found in Fica and Nagai () and Nguyen et al ().…”
Section: In Brief: 5′ Capping and Splicingmentioning
confidence: 99%